Metody budowy pojęcia zbioru w problemie interpretacji tez Hui Shi - Sikora, Sławomir (Investigationes Linguisticae, 2010)
The article presents an alternative conception of the problem of interpretation of the shortest and also most enigmatical text of Chinese philosophy, i.e. the ten theses of Hui Shi. Leśniewski claimed that the source of Russell’s dif-ficulties with antinomies is related to a lack of dis-tinction between a distributive and a collective class. Mereology is the logic of a certain concrete whole constituted by the parthood relations of a collective class. The use of Leśniewski’s formal solutions in the analysis of thesis (8) of Shi Hui: Linked rings can be disconnected, shows that in Chinese philosophical discourse two kinds of set theory were applied: distributive and collective. This is confirmed by thesis (5): When it is said that things greatly alike are different from things a lit-tle alike, this is what is called making little of agreements and differences; (when it is said that) all things are entirely alike or entirely different, this is what is called making much of agreements and differences. Therefore the hypothesis seems plausible that the paradox of Hui Shi’s theses was the result of a dual-istic formulation of the world order: on the one hand by the distributive order of distinguishing things by their names, on the other by the collective order of embracing all things within the frame of a common Universe.